Herbs In Treatment Covid 19, Recomended Or Not? - Purnamayanti, Ni Kadek Diah; Sutrisna, I Gusti Agung Adi; Kresnayana, Made Yos (Universitas Aisyah Pringsewu, 2021)
Since March 2020, Covid 19 has been declared as global health issue. In common knowledge a good immune is the antidot of the viral infection. The aim of study is to identify the used of herbs in treatment of Covid 19. Design of this study is systematic literature review. Inclussion criteria is only included human based experimental study. Exclussion criterias are review article, lab based study (pharmaetical network/ docking), and grey literature. Formulated keyword used “herbs AND immune AND Covid 19” in English and Bahasa Indonesia. Quality assesment in this study using JADAD Score. Based on online searching in 5 search enggines (Google Schoolar, Pubmed, SageJurnal, ScienceDirect and Garuda), there are 5 clinical trial in final result. There was 40% publised in Pyhtomedicine Journal and each 20% others published in Integrative Medicine Journal, American Blood Journal, Medtrix. The used of herbs in management of Covid 19 given as prevention in healthy people, complementary or alternative medicine in confirmed or suspected case.Implication on clinical practise , the herbs could be recommeded if the safety is proven by National Agency of Drug and Food Control. There was potential effect of herbs to reduced symptom of Covid 19.Abstrak: Sejak Maret 2020, Covid 19 telah dinyatakan sebagai masalah kesehatan global. Secara umum, kekebalan yang baik adalah penangkal infeksi virus. Tujuan dari penelitian ini adalah untuk mengidentifikasi penggunaan herbal dalam pengobatan Covid 19. Desain penelitian ini adalah studi literatur sistematis. Kriteria inklusi hanya termasuk studi eksperimental berbasis manusia. Kriteria eksklusi adalah artikel review, studi berbasis lab (jaringan farmasi/ docking), dan literatur abu-abu. Kata kunci yang diformulasikan menggunakan “herbs AND immune AND Covid 19” dalam Bahasa Inggris dan Bahasa Indonesia. Penilaian kualitas dalam penelitian ini menggunakan JADAD Score. Berdasarkan penelusuran online di 5 mesin pencari (Google Schoolar, Pubmed, SageJurnal, ScienceDirect dan Garuda), ada 5 uji klinis dalam hasil akhir. Ada 40% diterbitkan dalam Pyhtomedicine Journal dan masing-masing 20% lainnya diterbitkan dalam Integrative Medicine Journal, American Blood Journal, Medtrix. Penggunaan jamu dalam penanganan Covid 19 diberikan sebagai pencegahan pada orang sehat, pengobatan komplementer atau alternatif pada kasus konfirmasi atau suspek. Implikasinya pada praktik klinis, jamu dapat direkomendasikan jika terbukti keamanannya oleh Badan Pengawas Obat dan Makanan. Ada potensi efek herbal untuk mengurangi gejala Covid 19.